Ekologia rodziny w kontekście współczesnego społeczeństwa - Wojciech Bołoz (Studia Ecologiae et Bioethicae)
The family is a basic and solid part of a social structure, but it is always set in historical and cultural contexts, therefore over the centuries the family has been undergoing constant evolution: the form of the family and its functions change. In post-modern societies family standards are being more frequently abandoned in favour of so called “post-family” family which takes form of cohabitation and alternative ways of living: living alone, mono parentalship and homosexual partnerships.